Evaluating wrapping alpine ski boots during on-snow carving - Honert, Eric C.; Harrison, Kathryn; Feeney, Daniel (Frontiers in Sports and Active Living, 2023)
Alpine ski boots enable rapid and precise force transfer between skier and ski while carving. These boots are made of rigid plastic and fit tightly commonly through four buckles. Such a fit can improve speed and control, but also pain and discomfort. In athletic footwear, alterations to the upper designed to wrap the foot improve performance during rapid changes of direction and during trail running. The purpose of this study was to systematically evaluate the performance and fit of two different ski boot shell closure mechanisms: a BOA closure and a Buckle closure. This was a twopart study with 22 subjects performing on-mountain skiing and 10 of those subjects completing an inlaboratory pressure evaluation. Subjects skied in both boots three times each while data from inertial measurement units (IMUs) and plantar pressures were collected along with subjective data. In lab, static dorsal and plantar pressures were collected while the subjects flexed into the boots. This is the first study to systematically evaluate differences in ski boot closures. The BOA boots improved subjective and objective ski performance; qualitative carving scores were greater, likely through increasing the amount of normal force applied to the ski while turning. There were no differences in edge angles between the boots, as computed from IMUs. The BOA boot also reduced static peak plantar pressures in the rearfoot along with reducing overall static pressure on the dorsum as compared with the Buckle boot. The improvements in carving performance in the BOA boot are supported by distinct differences in pressure distribution within each boot, which we speculate contributed to improved performance by reducing discomfort or pain while still facilitating effective force transfer.